CEMARAN ASPERGILLUS FLAVUS PENGHASIL AFLATOKSIN B1 PADA JAGUNG MANIS (ZEA MAYS SACCARATA) YANG DIJUAL DI PASAR TRADISIONAL DAN PASAR MODERN DI KECAMATAN DENPASAR BARAT, KOTA MADYA DENPASAR – BALI - Akbar Napitupulu, Alief; Puspawati, Ni Nyoman; Kartika Pratiwi, I Desak Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2018)
This study aims to determine contamination, Aspergillus flavus in sweet corn sold in traditional and modern markets in West Denpasar district and to know whether A. flavus contaminating sweet corn can produce aflatoxin B1. The design of this study applied survey methods with sampling techniques of purposive sampling. Sampling determination was conducted on a number of markets, which were Traditional Markets and Modern Markets in West Denpasar District. West Denpasar District has 7 traditional markets and 3 modern markets. The variables observed were total mold of yeast, total mold, total of A. flavus, and aflatoxin content of B1. The results showed that the lowest A, flavus population was found on sweet corn sold in the traditional market sample which was <1 x 106 CFU/g. and the highest population was in the PKP sample of 7.0 x 106 CFU/g. The population of A. flavus in sweet corn sold in the modern market was <1 x 106 CFU/g. The result of aflatoxin test showed that the total samples taken in sweet corn merchants in traditional markets and modern markets in West Denpasar, 11 samples (34,37%) did not contain aflatoxin while 16 samples < 20 ppb (50%) contained aflatoxin B1 which was on samples of PBP1, PBP2, PPK, PKM1, PKM2, PBM1, PBM2, PBM3, PAS1, PAS2, PAS3, TD, GSR, SE, PKP, PBM2 and 5 samples (15,63%) were declared in accordance with BPOM and FDA regulations which was on samples PKM1, PAS1, PKP, GSR, and SE.